When Does Migration Law Discriminate Against Women?. (11th October 2021) - Briddick, Catherine
Abstract : It is possible to identify gendered disadvantage at almost every point in a migrant woman's journey, physical and legal, from country of origin to country of destination, from admission to naturalization. Rules which explicitly distribute migration opportunities differently on the grounds of sex/gender, such as prohibitions on certain women's emigration, may produce such disadvantage. Women may also, however, be disadvantaged by facially gender-neutral rules. Examples of indirectly disadvantageous provisions include those which classify certain forms of labor as either "low-" or "high-" skilled, using this categorization to distribute migration opportunities differentially. Such rules may disproportionately affect the mostly female workers whose labor in certain fields is considered "low-skilled" in comparison to that undertaken by their predominantly male, "high-skilled" counterparts. Scholars have identified the diverse ways in which states' immigration and nationality laws continue to involve gendered and racialized exclusion, subordination, and violence. Migration control practices, including those concerned with deterrence, detention, and deportation, have also been impugned on these bases. This essay draws on this literature to examine whether rules that produce gendered disadvantage are open to challenge under the international legal regime charged with eradicating discrimination against women, the Convention on the Elimination of all Forms of Discrimination Against Women (CEDAW).